Re‐evaluating the assistant practitioner role in NHS England: Survey findings. (22nd November 2018) - Kessler, Ian; Nath, Vandana
Abstract: Aim and Background: In the absence of data providing an overview on the state of the assistant practitioner (AP) workforce, this study surveys trusts in NHS England with the aim of establishing how the role is viewed, used and managed. Methods: Based on an earlier survey undertaken around a decade ago, an online questionnaire was sent to members of an assistant practitioner network, generating a response from over fifty different trusts, drawn from different regions and health care settings. Results: The survey results highlight the increased use of assistant practitioners by trusts and in a more diverse range of clinical settings. This increase has been driven more by the apparent value of the APs in addressing issues of service design and quality, than by attempts to reduce costs through substitution and skill mix dilution. Conclusions: The AP role has retained value to nurse managers in developing and designing services, and indeed in establishing a career pathway for health care assistants. Most striking are future intentions to continue using APs, particularly within the context of the emerging nursing associate (NA) role. This suggests that the AP and NA are likely to be complementary rather than alternative roles. Implications for Nursing Managers: Nurse managers might note the continuing use and value of the AP role, although as a means of improving design and quality as well as providing career opportunities for health care assistants, rather than as a way of saving labour costs. Clearly, the AP role has a future although there is scope to review its position in relation to the newly emerging nursing associate role.